2011
DOI: 10.3109/00016489.2011.622785
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the expression of NMDA, serotonin, and GAD in the central auditory system of the rat

Abstract: The total number of neuronal cell bodies of the CAS did not differ significantly at each level between young and aged rats (p > 0.05). Serotonin expression was increased with age in the IC and MGB, but decreased in the CN, SON, and AC (p < 0.05). NMDAR was significantly higher in the CN, MGB, and AC of aged compared with young rats, but was significantly decreased over time in the SOC and IC (p < 0.05). GAD67 was increased with age in the MGB and AC and decreased in the CN and SON (p < 0.05), but was not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This reduction in NMDA receptors (NMDARs) expression may be involved in the change of synaptic plasticity driven by the age-related decease in sensory input, resulting in age-related impairment in the function of the NMDAR/NO signaling pathway in the CNS [44]. However, in our study, the expression of NMDARs was increased in the CN, MGB, and AC during aging, although it was found that the expression of NMDARs was decreased in the superior olivary nucleus and IC [45]. Thus, these findings also indicated that age-related changes in the NMDARs in the central auditory system were region-specific.…”
Section: Regional Changes In Nadph-d In the Aging Brainmentioning
confidence: 56%
“…This reduction in NMDA receptors (NMDARs) expression may be involved in the change of synaptic plasticity driven by the age-related decease in sensory input, resulting in age-related impairment in the function of the NMDAR/NO signaling pathway in the CNS [44]. However, in our study, the expression of NMDARs was increased in the CN, MGB, and AC during aging, although it was found that the expression of NMDARs was decreased in the superior olivary nucleus and IC [45]. Thus, these findings also indicated that age-related changes in the NMDARs in the central auditory system were region-specific.…”
Section: Regional Changes In Nadph-d In the Aging Brainmentioning
confidence: 56%
“…Age influences both the density of serotonergic fibers and acute changes in serotonin, such that both fiber density and serotonin release during social encounters decline over young adulthood in mice (Hall et al, 2011; Papesh and Hurley, 2012). In older animals, serotonin content may rise again in the IC or other auditory regions (Cransac et al, 1996; Shim et al, 2012). Reproductive readiness, via gonadal hormones, also increases serotonergic fiber density in the avian auditory midbrain (Matragrano et al, 2012).…”
Section: Serotonin-auditory Plasticity; a Channel For Past Experiencementioning
confidence: 99%
“…Dynamic shifts in postsynaptic receptor expression accompany normal auditory learning (Sun et al 2005;Cai et al 2010) and development (Caicedo and Eybalin 1999;Kotak et al 1998;Sanes and Kotak, 2011). Agerelated hearing loss is accompanied by changes in GABA receptor distributions across the IC and ACtx (Gutiérrez et al, 1994;Milbrandt et al, 1994Milbrandt et al, , 1997Raza et al, 1994;Caspary et al, 1995Caspary et al, , 2013Yu et al, 2006), alongside changes in NMDA receptor distributions (Shim et al, 2012). Further, acute cochlear trauma leads to altered distributions of excitatory and inhibitory postsynaptic receptors in the brainstem (Suneja et al, 2000;Dong et al, 2009Dong et al, , 2010a, IC (Holt et al, 2005;Dong et al, 2010b), and ACtx (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%